Anthropology and climate change: From transformations to worldmaking - Crate, Susan A.; Nuttall, Mark (New York Routledge, 2024)
In this third edition of Anthropology and Climate Change, Susan Crate and Mark Nuttall offer a collection of chapters that examine how anthropologists work on climate change issues with their collaborators, both in academic research and practicing contexts, and discuss new developments in contributions to policy and adaptation at different scales. Building on the first edition$1 (Bs pioneering focus on anthropology$1 (Bs burgeoning contribution to climate change research, policy, and action, as well as the second edition$1 (Bs focus on transformations and new directions for anthropological work on climate change.s